Post a New Question


posted by .

Use Hess's law and the following equations to calculate ÄH for the reaction N2(g) + 2O2(g) N2O4(g).

2NO2(g)->N2O4(g) ÄH = –57.0 kJ/mol

N2(g)+O2(g)->2NO(g) ÄH = 180.6 kJ/mol

2NO2(g)->2NO(g)+O2(gÄH = 114.4 kJ/mol

  • chemistry -

    I didn't do this with a pencil and pad but try this
    Add equn 1 to equan 2 to the reverse of equan 3 and see if that won't give you the equation you want. For the dH values, change the sign of those you reverse.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question